The Effect of Audio-Visual Media on Students' Learning Motivation on Islamic History Materials - Siti Munawaroh; Djunaidi Ghany; Syaad Patmanthara (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The use of audio-visual media is considered an activity that can attract students' attention during teaching and learning activities. Audio-visual media is expected to be a medium that helps students understand the material and enjoy learning. These conditions, of course, aim to increase students' learning motivation to improve the quality of learning in the classroom, especially for PAI subjects. So, in the proof, the researcher wants to test the effect of audio-visual media on students' learning motivation in Islamic History Materials for Class V MI Mambaul Ulum Pakis Malang students. The research approach used in this research is quantitative research. Namely, research methods based on the philosophy of positivism are used to examine specific populations or samples. The research design used in this study was a quasi-experimental research design (Quasi Experiment) which involved one group of research objects. Then test the homogeneity of variance using Levene's equality of error variances test. Audio-visual learning media affects the learning motivation of fifth-grade students at MI Mambaul Ulum Pakis Malang. The paired t-test analysis results showed that the student's learning motivation before and after using audio-visual learning media was different from the t-test result of 4.01 with a significance level of 0.000 <0.05. The effectiveness of increasing the learning motivation of fifth-grade students at MI Mambaul Ulum Pakis Malang before and after using audio-visual learning media can be shown from the increase in the student learning motivation questionnaire results by 35.22% and the observation results of student learning motivation by 44.86%.